2020
DOI: 10.3390/nu12092863
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Dietitian Referrals in Hospitals

Abstract: Dietitian involvement has considerable benefits for hospitalized patients, resulting in better health outcomes and improved quality of life. However, dietitian referral routines are often inappropriate in hospitals. The aim of this study was to identify predictors for dietitian referrals in hospitalized patients. This study was performed on data collected in an annually conducted cross-sectional study (in the years 2017, 2018, 2019). A standardized questionnaire was used to collect data, and logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…European, US and Australian best practice guidelines all recommend nutrition risk screening using a validated tool and subsequent referral to a dietitian for those identified at risk for all hospital patients. 4,31,32 The dietitian referral rate of 45% for those 'at risk' of malnutrition is consistent with an international 45-hospital study involving 8405 patients reporting that 37% of people at risk of malnutrition were referred to a dietitian, 6 as well as an Australian study reporting that 45% of individuals at risk of malnutrition were being managed by a dietitian. 7 Together, these findings indicate that best practice standards for management of malnutrition are not being achieved.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…European, US and Australian best practice guidelines all recommend nutrition risk screening using a validated tool and subsequent referral to a dietitian for those identified at risk for all hospital patients. 4,31,32 The dietitian referral rate of 45% for those 'at risk' of malnutrition is consistent with an international 45-hospital study involving 8405 patients reporting that 37% of people at risk of malnutrition were referred to a dietitian, 6 as well as an Australian study reporting that 45% of individuals at risk of malnutrition were being managed by a dietitian. 7 Together, these findings indicate that best practice standards for management of malnutrition are not being achieved.…”
Section: Discussionsupporting
confidence: 62%
“…2,3,5 A 2020 cross-sectional study across 45 Austrian hospitals over three years found that malnutrition screening was inadequate or not completed in 50.2% of the study population (n = 8405 individuals). 6 In this study, 46.6% of people identified as at risk of malnutrition through screening were not referred to a dietitian. 6 Similar findings were reported in an Australian study published in 2012.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Alternately, it may be that the form innovations take in health professionals’ practice differ from the form innovations take in other studied professions and that innovation in the health professions is well-served by both achievement and dependability. Dietetics, specifically, is a small health profession whose members report feeling as though their role is undervalued 102,103 (including monetarily 104 ) and misunderstood 51,103,105 ; thus, there are strong incentives to be dependable and to avoid rocking the boat. 106 Providing consistent, high-quality care may appear to be the safest path to recognition and clarity surrounding the roles of small health professions among interdisciplinary team members.…”
Section: Discussionmentioning
confidence: 99%